Solomon Islands : First Review Under the Extended Credit Facility Arrangement-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Solomon Islands. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses Solomon Islands' First Review Under the Extended Credit Facility (ECF) Arrangement. The three-year arrangement under the ECF is on track. All December 2012 and continuous performance criteria have been met, except for the cash balance floor, which was temporarily missed by a small amount. The indicative target on health and education for December 2012 was also missed by a very small margin. The IMF staff recommends completion of the review and supports the authorities' request for a waiver of the nonobservance of the cash balance floor at end-December, and the modification of end-June 2013 performance criteria.